Organizational Competitiveness and Digital Governance Challenges - Tiwari, Siddhartha Paul (Archives of Business Research, 2022)
Digital governance improves the efficiency of the system in general, resulting in improved business and merchandising performance. The purpose of digital governance has always been to make life easier for people and to improve the level of satisfaction of customers. In response to the recovery of the markets, organizations around the globe are now playing a different role. The role of digital governance at the moment is largely one of facilitation rather than of regulation. It is true that digital has been around for some time, but there is still a lot of work to be done to fully realize its potential. The purpose of this paper is to explain how concrete elements of digital governance can affect the competitiveness of businesses. Thus, this was a key element for the successful recovery of the markets following the era of Covid. This is despite the fact that it has been around for so long. In order for a company to successfully compete in international markets and maintain quality, its level of productivity performance in comparison with its competitors plays a very significant role.